Diagnostic challenges due to phenocopies: lessons from Multiple Endocrine Neoplasia type1 (MEN1). - Turner, J; Christie, P; Pearce, S; Turnpenny, P; Thakker, R (2010)
Phenocopies may confound the clinical diagnoses of hereditary disorders. We report phenocopies in Multiple Endocrine Neoplasia type 1 (MEN1), an autosomal dominant disorder, characterised by the combined occurrence of parathyroid, pituitary and pancreatic tumours. We studied 261 affected individuals from 74 families referred with a clinical diagnosis of MEN1 and sought inconsistencies between the mutational and clinical data. We identified four patients from unrelated families with phenocopies. Patients 1 and 2 from families with MEN1, developed prolactinomas as the sole endocrinopathy but they did not harbour the germline MEN1 mutation present in their affected relatives. Patient 3, had acromegaly and recurrent hypercalcaemia following parathyroidectomy, whilst patient 4 had parathyroid tumours and a microprolactinoma. Patients 3 and 4 and their relatives did not have MEN1 mutations, but instead had familial hypocalciuric hypercalcaemia (FHH) due to a calcium-sensing receptor mutation (p.Arg680Cys), and the hyperparathyroidism-jaw tumour (HPT-JT) syndrome due to a hyperparathyroidism type 2 deletional-frameshift mutation (c.1239delA), respectively. Phenocopies may mimic MEN1 either by occurrence of a single sporadic endocrine tumour in a patient with familial MEN1, or occurrence of two endocrine abnormalities associated with different aetiologies. Phenocopies arose in >5% of MEN1 families, and awareness of them is important in the clinical management of MEN1 and other hereditary disorders.